Design and control of a bidirectional interlinking converter for energy storage system - Liu, Jiazhe (2017)
Renewable Energy Sources (RES) generation is developing in recent years, which is sustainable and clean. However, they also caused lots of problems in power grid’s stability, such as the difficulty of frequency regulation. Because RES generation like wind power and solar power are immensely influenced by weather condition, the output of generation will change and it will break the balance between power supply and demand. Finally, it will lead to the frequency drop in the power system. Besides, some of the wind generators and solar generators cannot provide inertia to power system as traditional generators. Thus, RES generation is detrimental to frequency stability of the power system. To keep the frequency stable, the bidirectional interlinking converter is used as an interface between power grid and energy storage to realize bidirectional energy transfer. By compensating power grid for active power, the change of frequency can be mitigated. This project aims to design the hardware and the control system of such a bidirectional interlinking converter. Firstly, the basic knowledge related to the design was introduced. Secondly, the hardware of bidirectional converter, PWM converter, and controllers of DC voltage and current are designed. Thirdly, the model of the bidirectional converter was built up in Matlab and its control system was tested in Matlab. Finally, the downscaled prototype of the converter was built up and be tested with Matlab and dSPACE.